Proposal for the teaching of saponification reaction allies with environmental - Alexandre, Maria Eduarda da Silva; Dias, Mauro Cesar; Filomeno, Claudinei Andrade (Brazilian Journal of Production Engineering, 2023)
The teaching of Chemistry still has many obstacles, since students reject the subject as they cannot relate it to their everyday phenomena. Environmental education (EE), even if it is of utmost importance, is also a topic that is little bit explored by teachers in the classroom. That way, this present work aims to combine the teaching of the saponification reaction with EE through a practical lesson and the creation of pedagogical materials to be applied and validated in a public high school. The work aims to fulfill the requirements of the "EM13CNT101" and "EM13CNT104" competencies of the National Common Core Curriculum (BNCC). The application proved to be effective and satisfactory, as more than 60% of the 44 students who participated until the end affirmed that they learned about recycling of residual frying oil (RFO) and the chemical aspects related to soap production, they also affirmed that the materials and the practical lesson are interesting and were able to connect chemistry with EE. That way, it can be concluded that the work successfully achieved the proposed objective based on the competencies of BNCC, since students were able to develop a greater socio-environmental responsibility.